Late modern English novel encounters - Kytö, Merja; Smitterberg, Erik (Studies in language companion series,, 2020)
"The past few decades have witnessed an unprecedented surge of interest in the language of the Late Modern English period. Late Modern English: Novel Encounters covers a broad range of topics addressed by international experts in fields such as phonology, morphology, syntax, lexis, spelling and pragmatics; this makes the collection attractive to any scholar or student interested in the history of English. Each of the four thematic sections in the book represents a core area of Late Modern English studies. This division makes it easy for specialists to access the chapters that are of immediate relevance to their own work. An introductory chapter establishes connections between chapters within as well as between the four sections. The volume highlights recent advances in research methodology such as spelling normalization and other areas of corpus linguistics; several contributions also shed light on the interplay of internal and external factors in language change"--